Ethernet Control AC Motor via PLC using LabVIEW - Barsoum, Nader; Chin, Pin Rui (Scientific Research Publishing, 2011)
Remotely control applications over a wide area had been commonly used in the industries today. One of the common applications requires remote control and monitoring is inverter fed induction drive system. Drive system has various types of controller, in order to perform some actions such as control the speed, forward and reverse turning direction of the motor. This approach can be done by Programmable Logic Controller (PLC), and with the rise of the technology, Ethernet module will be used in order to achieve the remote con-trol system. Plus the PLC today can be controlled not only using its original software, but 3rd party software as well, such as LabVIEW. LabVIEW is a human machine interfaces design software that is user friendly. It can be easily communicate with different hardware.